FirstLight - II. Star formation rates of primeval galaxies from z=5-15 - Ceverino, Daniel; Klessen, Ralf S.; Glover, Simon (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. In the FirstLight project, we have used ∼300 cosmological, zoom-in simulations to determine the star formation histories of distinct first galaxies w
Advance access publication 2018 August 03
Gesehen am 08.04.2019